Clamping method and mechanical properties of aluminum honeycomb cylindrical curved plates under radial compression. (November 2022) - Song, Yiheng; Lin, Qinyu; Chen, Jinxiang
To develop a new type of bionic curved sandwich plate, it is necessary to first develop experimental methods and evaluation criteria for curved plates. Thus, this paper focuses on an aluminum cylindrical honeycomb plate and proposes two types of clamping methods for radial compression tests. Using finite element simulation, radial compression tests were carried out, and the mechanical characteristics under different clamping methods were studied. The results showed that (1) the two types of clamping methods have significant effects on the radial compression performance, and each has its own characteristics. The influence mechanism was explored from the perspective of the deformation shape of the sample and the sliding direction of the foot. (2) Clamping methods were given with regard to different experimental purposes or engineering application objects (backgrounds), and three clamping methods that are easy to prepare and have great universality were also presented. This research provides an important theoretical basis for the development of curved plates, radial compression test methods for curved plates and the formulation of corresponding test standards.